Board Resignation Impact on Limited Liability Company Going Concern: Absence of Provisions - Suhardiman, Daniel; Pramono, Nindyo (Global Legal Review, 2023)
In Indonesia, matters concerning limited liability companies is mainly governed by Law Number 40 of 2007 on Limited Liability Company (Companies Law). The Companies Law regulates all aspects from the formation of company until the dissolution of company along with the legal consequences. In forming a limited liability company, a company must be formed by 2 (two) or more people. This mandatory provision creates the practice of a limited liability company with 50-50 shareholder composition, especially for private company. Structurally, a limited liability company consists of General Meeting of Shareholders (GMS), the Board of Directors (BOD), and the Board of Commissioners (BOC). Both members of BOD and BOC serve the company with limited terms of office and shall be re-appointed by the GMS. In practice, there is a condition where the GMS fails to re-appoint or replace the BOD and BOC even when all the members of BOD and BOC’s terms of office have been ended. During this period, those members of BOD and BOC can no longer act on behalf the limited liability company. The possibility of such company facing such situation is quite high, especially if the company’s shareholder composition is 50-50. This research aims to discuss and analyse the BOD and BOC whose terms of office have ended without re-appointment or replacement by the GMS. The result shows that since the Companies Law has yet to regulate provision to overcome the described issue, this condition may endanger the operation and the existence of limited liability company. Consequently, the existing Company Law has to be amended to address the aforementioned issue.